2022
DOI: 10.3855/jidc.13064
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide and Brazilian scientific publications on Leishmaniasis in the first 19 years of 21st century: a bibliometric study

Abstract: Introduction: Leishmaniasis is a set of tropical diseases widely distributed throughout the world. Publications concerning different aspects of leishmaniasis have shown an increasing trend in recent years, especially in Brazil, where this disease has been under continuous expansion. The present study analyzes the data and assess trends in publications on leishmaniasis in Brazil and worldwide. Methodology: The bibliometric analysis was performed on the Scopus database, addressing data on scientific public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…These are also major markets of protection. This finding is consisting with the outstanding contribution of Brazil, the USA and India to leishmaniasis research [21][22][23][24][25], the fact that these countries are endemic for leishmaniasis [26] and that China and the USA are the leading countries in overall patent filings and filings by residents [27]. The expressive contribution of Brazil and India is also in line with the impact of the disease in these countries.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…These are also major markets of protection. This finding is consisting with the outstanding contribution of Brazil, the USA and India to leishmaniasis research [21][22][23][24][25], the fact that these countries are endemic for leishmaniasis [26] and that China and the USA are the leading countries in overall patent filings and filings by residents [27]. The expressive contribution of Brazil and India is also in line with the impact of the disease in these countries.…”
Section: Discussionmentioning
confidence: 79%
“…Our patent data analyses indicate that the strong international collaborative research observed when analyzing scientific publications on leishmaniasis worldwide [ 23 , 25 ] does not lead to co-ownership of patent applications for leishmaniasis diagnosis. In fact, only 16% of our patent families contained some type of joint research (international or national), the vast majority of which occurred between two academic institutions from the same country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis using bibliometrics has existed since the early 20th century [38]- [40]. The term "bibliometrics" refers to a statistical method for compiling information about publications' authors, institutions, journals, and other relevant sources [41]. Due to the growing body of literature on a specific subject, it is helpful to employ a variety of quantitative rubrics to assess the most critical developments in that field [42].…”
Section: Reseacrh Methods 31 Bibliometric Analysismentioning
confidence: 99%
“…Implementation of effective protective measures demands knowledge of the characteristics of notifications and the epidemiology of the disease, particularly regarding the spatial and temporal patterns of new cases, which better indicate the transmission patterns [ 18 , 19 ]. However, literature concerning the epidemiology of TL in Brazil is based predominantly on data from local surveys [ 19 , 20 ] and there are no studies that evaluated the spatial and temporal patterns of TL in the country over 20 years at the subnational level.…”
Section: Introductionmentioning
confidence: 99%